Software certification and its implementation in Malaysian software industry: A survey - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz; Mohd, Haslina (American Scientific Publishers, 2013)
This paper discusses about the outcome from a survey which was conducted among Malaysian software practitioners regarding software certification and its implementation.Very few studies have been conducted in the South East Asia region regarding this issue.Thus, this survey was conducted to investigate the software practitioners' practices and perceptions on the software certification and its implementation in real-world projects. For data collection, structured questionnaire was used, whilst for data analysis simple statistical methods which are frequency and cross tabulation were utilized.The findings from this study revealed that software certification is needed to enhance the quality of produced software.One of the reasons is that the software practitioners are neglecting good software development practices, which directly influences the quality of produced software.Thus, by conducting software certification, the customers will be more confident with the quality of software produced for them, as it involves independent assessment.Therefore, it prolonged the needs of our study in constructing a process based software certification model.Consequently, the outcomes of this study will contribute to the development of the proposed model.